Anisa Puspitasari Tradisi Kupatan Dalam Ritual Rebo Wakasan Perspektif Living Qur'an - Anisa Puspitasari (Universitas Islam Syekh-Yusuf, 2023)
This writing aims to find out how the process of the kupatan tradition in the Rebo Wakasan ritual and also the author tries to examine the kupatan tradition in the Rebo Wakasan ritual from the perspective of living qur'an in Cikalahang Village, Pabuaran Village. This research uses a qualitative research method with a case study approach that relies on collecting secondar and primary data sources. Secondary data obtained through literature studies, such as journals or articles, books and other reading materials and primary data sources include observations and interviews. The results of this study show that in the perspective of living qur'an, the Rebo Wakasan ritual is seen as a community response to the Qur'an. Phenomena contained in the Rebo Wakasan ritual in Cikalahang village such as: Prayers, dhikr, praying, giving alms and reading surahs of the Qur'an together are the result of the interpretation of the Cikalahang village community on the function of the Qur'an which according to them can protect from various disasters by the will of Allah SWT